1977
DOI: 10.1088/0031-8949/15/2/003
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Determination of Electron Momentum Densities

Abstract: Recent developments and the current state of experimental methods for the determination of electron momentum densities (EMD's) are reviewed. The remarkable growth both in applications of traditional techniques as well as in the development of new techniques over the last three years is described. A general analysis of the determination of EMD's in atoms, molecules and solids provides the context within which the recent work is discussed. This leads to a consideration of the physical information contained in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“…It was concluded that reproducibility of ± 1 % of the peak height of the profile is quite feasible, and that in a differential experiment ±0.5 % or even better is possible. The techniques are extensively reviewed in Williams (1977b), with further details in the chapters in Williams (1977a) by Halonen et al (1977), Mendelsohn and Smith (1977) and by Berggren et al (1977).…”
Section: S-matrix Incoherent Scattering Theorymentioning
confidence: 99%
“…It was concluded that reproducibility of ± 1 % of the peak height of the profile is quite feasible, and that in a differential experiment ±0.5 % or even better is possible. The techniques are extensively reviewed in Williams (1977b), with further details in the chapters in Williams (1977a) by Halonen et al (1977), Mendelsohn and Smith (1977) and by Berggren et al (1977).…”
Section: S-matrix Incoherent Scattering Theorymentioning
confidence: 99%
“…Furthermore, momentum quantities may be useful in quantum mechanics to interpret experimental results such e.g. Compton profiles [28], cross sections from (e, 2e) spectroscopy [20], etc.…”
Section: Hartree-fock Equations In Momentum Spacementioning
confidence: 99%
“…Both the momentum distribution and Compton profile are powerful probes for understanding the ground state properties of materials. The momentum distribution of the electrons can be experimentally studied by scattering methods such as Compton scattering, positron annihilation, the (e, 2e) process and high energy electron scattering [28][29][30][31]. In general, the differential cross sections can be related to the momentum distribution.…”
Section: Introductionmentioning
confidence: 99%